Evidence brief: Planning now for the future of technology-enabled healthcare work in Ontario - Moat, KA; Lavis, JN (My University, 2023)
A synthesis of what is known, based on the best available global and local research evidence about the problem(s) related to planning now for the future of technology-enabled healthcare work in Ontario, elements of a potentially comprehensive approach for addressing it, and key implementation considerations. This evidence brief was prepared to inform a stakeholder dialogue.
Keywords: planning; future; technology-enabled; healthcare; Ontario